Analysis of MHD hybrid nanofluid flow over cone and wedge with exponential and thermal heat source and activation energy - Alshehry Azzh Saad; Noor Saima; Abas Syed Arshad; Fiza Mehreen; Ullah Hakeem (Open Physics)
Hybrid nanofluids, an advanced class of working fluids, gained significant attention due to their superior thermal performance and heat transfer characteristics. These fluids consist of two types of nanoparticles suspended in a base fluid, offering enhanced thermal performance, making them crucial in engineering applications. In many industrial processes, magnetohydrodynamic (MHD) hybrid nanofluid flow plays a vital role in controlling mass and heat transfer in systems involving precipitation and chemical processing. The interaction between thermal radiation, chemical reactions, Joule heating, and heat sources significantly affects the efficiency of such systems, necessitating an in-depth analysis of their combined effects. This study focuses on the heat and mass transfer in hybrid nanofluid flow over various geometries, which is crucial for thermal management in electronic devices, precipitation, and filtration processes. Practical applications of a hybrid nanofluid flow around cones and wedges include spacecraft design, nuclear reactors, solar power collectors, etc. Therefore, this research examines the MHD hybrid nanofluid flow over a cone and wedge, using a suspension of SWCNTs and MWCNTs as nanomaterials in H2O as the base fluid. The study also considers the impact of Joule heating, an exponential space-based heat source in the temperature equation with thermal and mass convective conditions over two geometries (cone and wedge). Additionally, chemical reactions play a significant role in various natural and industrial processes. With this initiation, this research explores the effect of the activation energy and binary chemical reaction on the MHD hybrid nanofluid flow. The hybrid nanofluid model over two different geometries is governed by partial differential equations and converted to ordinary differential equations using similarity variables. The bvp4c method in MATLAB was employed to solve these equations numerically. The effects of the sundry flow parameter on the velocity, temperature, and concentration distributions were determined and discussed briefly. The study’s findings show that the improvement in both the thermal and mass Grashof numbers results in an increase in the velocity profile, supporting the effectiveness of hybrid nanofluids in cooling technologies for electronic devices. The increasing impression of the activation energy and mass Biot number on the concentration profile is progressive for wedges compared to cones. Furthermore, the results reveal that the presence of a nonlinear heat source tends to intensify the thermal profiles for wedges more significantly than the flow over cones, which is also related to the application of solar power collectors. The rate of heat transfer for the flow over a cone case is higher for the growing estimation of radiation, and the Biot number is particularly relevant to high-temperature applications such as nuclear reactors and spacecraft. The increasing impact of the Schmidt number, chemical reaction, and mass Biot number on the mass transfer rate is higher for cones as compared to wedges, while the activation energy has an opposite behavior for both flow cases. The observed trends in the mass transfer rate also support filtration and separation technologies, optimizing their efficiency based on fluid and material properties.